2008
DOI: 10.3748/wjg.14.1383
|View full text |Cite
|
Sign up to set email alerts
|

Management of cholelithiasis in Italian children: A national multicenter study

Abstract: development of complications was reported. CONCLUSION:The therapeutic strategies were extremely heterogeneous. Ursodeoxycholic acid was ineffective in dissolution of gallstones but it had a positive effect on the symptoms. Laparoscopic cholecystectomy was confirmed to be an efficacy and safe treatment for pediatric gallstones. INTRODUCTIONIn the last years following the extensive use of ultrasound scanning an increasing number of children with cholelithiasis has been identified. In a population based study, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
2
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 25 publications
(30 reference statements)
2
36
2
12
Order By: Relevance
“…The incidence of idiopathic cholelithiasis in other reported series varies from 23 to 52.5%. [56] The trend of the increasing incidence of non-haemolytic cholelithiasis is also reflected in our series, with all of them belonging to the non-haemolytic cholelithiasis category. The mechanism of gallstone formation in these children is probably due to a combination of interacting processes, including, dehydration, transient hepatic dysfunction, dietary, inflammatory, hereditary and endocrine influences, which affect the composition of bile.…”
Section: Discussionsupporting
confidence: 66%
“…The incidence of idiopathic cholelithiasis in other reported series varies from 23 to 52.5%. [56] The trend of the increasing incidence of non-haemolytic cholelithiasis is also reflected in our series, with all of them belonging to the non-haemolytic cholelithiasis category. The mechanism of gallstone formation in these children is probably due to a combination of interacting processes, including, dehydration, transient hepatic dysfunction, dietary, inflammatory, hereditary and endocrine influences, which affect the composition of bile.…”
Section: Discussionsupporting
confidence: 66%
“…33 Gumiero et al observed in their study that 88 patients had multiple stones and 12 patients had one single gallstone. 24 Dooki and Norouzi reported in their study that 19 (29%) patients had solitary gallstones and in 47 patients (71%) there were multiple gallstones, moreover 3% of the patients had stones simultaneously in the common bile duct (CBD) and 1.5% in cystic duct. 30 Furthermore, 52 patients (65%) had mixed stones.…”
Section: Discussionmentioning
confidence: 96%
“…Familiarity has also been reported in other studies. 8,24 Association of junk food consumption with childhood cholelithiasis could not be established. Obesity in many studies has been documented as major risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Erişkin serisinden farklı olarak çocuk hastaların yarısından fazlasında ameliyat önce-si dönemde ursodeoksikolik asit tedavisi başlanmıştı. Çocukluk çağında, asemptomatik veya tesadüfen saptanan safra taşlarına çoğunlukla cerrahi müdahale gerekmez, ancak gerekirse açık cerrahi yerine laparoskopik yaklaşım tercih edilmektedir (10) . Safra kesesi taşları hem erişkinlerde daha sık rastlanmakta hem de kolesistit oluşumu ile semptomatik hâle gelmektedir.…”
Section: Discussionunclassified